Effects Of A Guided Cooperative Experiential Learning Strategy In Flipped Classroom On Students’ Participation, Performance, And Perception In Learning English - Jamal Mydin, Azrina P. (2023)
Malaysian students lack the skills to speak proper English. The issues include the current teaching and learning strategies applied in schools that focus on textbooks as the medium of instruction, discouraging the development of higher order thinking skills among secondary school students, resulting to a passive learning environment. This subsequently has affected the development of English language skills especially speaking and writing. This study aimed to determine the effect of the flipped classroom with the integration of Cooperative Experiential Learning (CEL) strategies, to improve student’s participation and performance (writing and speaking) in English and to gauge their perception of the intervention. Research sample were 95 form 4 students from two all girls’ schools. Three groups (full-flipped, semi-flipped and control group) were selected based on cluster and random sampling. A quasi-experimental design was employed incorporating qualitative and quantitative data collection methods. Instruments used were pre-test, post-test, perception questionnaire, presentation and participation rubric. Data were analyzed using descriptive statistics, independent sample t -test, one-way ANCOVA and ANOVA.